Pengaruh Nilai Tukar Terhadap Harga Saham Sektor Keuangan yang Terdaftar di Bursa Efek Indonesia - Gunardi; Nugraha; Sugiyanto (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2020)
The exchange rate is macroeconomic that is important for the sustainability of the economy in a country, previous research shows the effect of the exchange rate on stock prices. These conditions indicate that investors view the exchange rate as a signal to a country's economy, so investors consider the exchange rate to make investments. This study uses a quantitative approach that is tested by multiple regression to determine the effect of exchange rates on stock prices, the data of this study are from January 1, 2020, to May 8, 2020, the data collection is based on the state of the world economy that is weakening due to the COVID-19 outbreak. The results show that the exchange rate has an influence on the stock prices of the financial sector which are listed on the Indonesia Stock Exchange, these results have similarities and differences with the results of research in other emerging market countries.